CHANGING DIMENSIONS OF CASTE AND ELECTORAL POLITICS IN BIHAR - Manish; Sanjeev (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the changes in electoral politics in India since independence, particularly focusing on the growing participation of marginalised groups, especially Dalits and Other Backward Classes (OBCs), in the democratic process, particularly in Bihar. Pre-independence electoral politics was dominated by upper class and upper caste leaders, but figures such as Dr. B. R. Ambedkar advocated the political empowerment of the disadvantaged classes. This article divides the evolution of this movement into two main phases: the first, from 1967 to 1990, which focused on the political empowerment of OBCs and Dalits in regions such as Uttar Pradesh and Bihar, with figures such as Karpoori Thakur, Kanshi Ram and Ram Manohar Lohia playing key roles. It also analyses the political volatility of Bihar during this period, including the shift in the balance of power between leading and backward castes, the rise of caste-based activism, and the influence of money and power.